Adaptation and Validation of the Serbian Version of Dyslexia Screening Test-Junior - Tanja Lukovac; Vitomir Jovanović; Svetlana Petronijević; Jovana Radović; Neda Milošević Dedakin; Tatjana Savić; Dragan Pavlović (Children)
Background/Objectives: Dyslexia, a prevalent reading disorder, substantially affects children’s educational and social development. Early diagnosis is essential for timely intervention; however, Serbia lacks a standardized instrument for assessing dyslexia in primary school children. This study aimed to evaluate the reliability and predictive validity of the Dyslexia Screening Test-Junior (DST-J), which was adapted for the Serbian language and cultural context. Methods: The study sample comprised 647 children from the general population, aged 6 years and 6 months to 11 years and 5 months, along with 30 children of comparable age exhibiting reading difficulties. The assessment of validity was based on the at-risk quotient, predictive validity, and test–retest reliability. Results: Significant differences in at-risk quotient (ARQ) scores were found between children with and without dyslexia (t = 14.90, p < 0.001), with boys, particularly those aged 9.6 to 10.5 years, having higher risk scores than girls. Internal consistency was acceptable (Cronbach’s α = 0.704), and construct validity was confirmed by correlations with external measures, which explained 44% of the variance (R2 = 0.44; p < 0.01). Predictive validity was high for key subtests such as rapid naming and phonemic segmentation, reaching maximum accuracy (sensitivity and specificity = 1). Conclusions: The findings indicate that the adapted DST-J is effective in identifying dyslexia risk among Serbian primary school children. The innovation of this study lies in the cultural adaptation of the DST-J, with future research directed towards refining this instrument and exploring additional diagnostic criteria to enhance its accuracy and inclusivity.